2021
DOI: 10.1038/s41389-020-00293-9
|View full text |Cite|
|
Sign up to set email alerts
|

PBK phosphorylates MSL1 to elicit epigenetic modulation of CD276 in nasopharyngeal carcinoma

Abstract: CD276 (also known as B7–H3, an immune checkpoint molecule) is aberrantly overexpressed in many cancers. However, the upregulation mechanism and in particular, whether oncogenic signaling has a role, is unclear. Here we demonstrate that a pro-oncogenic kinase PBK, the expression of which is associated with immune infiltration in nasopharyngeal carcinoma (NPC), stimulates the expression of CD276 epigenetically. Mechanistically, PBK phosphorylates MSL1 and enhances the interaction between MSL1 and MSL2, MSL3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…In the correlation analysis of PBK and immune checkpoints, PBK is significantly correlated with VSIR, NRP1, TNFRSF14, LAIR1, CD47, CD200, and CD276. Consistent with recent study, Wang et al (2021) suggested that PBK promotes the CD276 transcription through the enrichment of the MSL complex, which plays an important role in the immune evasion of nasopharyngeal carcinoma (NPC), and may serve as a biomarker for cancer immunotherapy. This suggests that PBK expression might be relevant to the immunotherapy in these immune checkpoints.…”
Section: Discussionsupporting
confidence: 79%
“…In the correlation analysis of PBK and immune checkpoints, PBK is significantly correlated with VSIR, NRP1, TNFRSF14, LAIR1, CD47, CD200, and CD276. Consistent with recent study, Wang et al (2021) suggested that PBK promotes the CD276 transcription through the enrichment of the MSL complex, which plays an important role in the immune evasion of nasopharyngeal carcinoma (NPC), and may serve as a biomarker for cancer immunotherapy. This suggests that PBK expression might be relevant to the immunotherapy in these immune checkpoints.…”
Section: Discussionsupporting
confidence: 79%
“…PBK expression was positively correlated not only with immune infiltration cells including M2 macrophage, Tregs, CAFs, and MDSCs but also with T-cell exhaustion, which are involved in tumor immune escape [24,34]. Similarly, Wang et al suggested PBK/MSL1/ CD276 signaling axis, which may play an important role in immune evasion of nasopharyngeal carcinoma and may be targeted for cancer immunotherapy [12]. Huang et al identified PBK as one of the 14 hub genes correlated with immune cell infiltration in LIHC [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several recent studies have suggested that PBK/TOPK may be associated with tumor-infiltrating immune cells and have a potential target for cancer immunotherapy [5,11,12]. is study is the first to conduct a pancancer analysis of PBK/TOPK using Oncomine, Human Protein Atlas(HPA), ULCAN, the Tumor Immune Estimation Resource 2.0 (TIMER2.0), STRING, Gene Expression Profiling Interactive Analysis 2 (GEPIA2), and the data collected from e Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression Project (GTEx).…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulation of CD276 following PBK-overexpression could be reversed by MSL1 depletion. Mechanistically, MSL1 serves as a mediator in the PBK-MSL1-CD276 axis (39). Overall, there are many intertwined factors contributing to the regulation of CD276 expression, which result in the observed relatively low level expression in normal tissue and elevated expression in tumor tissue.…”
Section: Regulatory Mechanisms Of Cd276mentioning
confidence: 99%